Effects of the Covid-19 pandemic on the incidence of care provided to patients who are victims of sexual violence in a reference hospital in Teresina-PI (Research, Society and Development, 2023)
Violence against women constitutes one of the main forms of violation of their human rights, affecting their rights to life, health and physical integrity. The present study aims to analyze the effects of the Covid-19 pandemic on the incidence of care provided to women victims of sexual violence at the Dona Evangelina Rosa maternity hospital in Teresina-PI. Currently, sexual violence is a universal phenomenon, affecting women of all social classes, ethnicities, religions and cultures. It occurs in populations with different levels of economic and social development, in public and private spaces and at any stage of a woman's life, with negative repercussions in different categories of life, which may or may not be reversible. In view of the results found above, it was concluded that sexual violence against women is still a public health problem that occurs in large proportions in Brazilian society. There are many cases that are underreported, generating contradictory estimates found in the literature. The incomplete completion of notifications makes it difficult to collect more accurate data on the profile of the victims, because sexual violence is capable of generating disturbances in the short and long term, leaving deep sequelae, impacting the physical, psychological and social health of the victim, considering that most women are young adults, in the reproductive period, on economic and social ascension who are in search of self-sufficiency.